Al-Lughah Al-‘Arabiyyah wa At-Thuqus Ats-Tsaqafiyyah Lada Al-Muslimin fi Tahqiq Al-Marasim Ad-Diniyyah - Hilmi, Danial (UIN Maulana Malik Ibrahim Malang, 2017)
اللغة العربية هي لغة متصفة بالثقافة الإسلامية التي تتحقق في الطقوس الثقافية بالقيام بالتعبد لله تعالى في الطاعات للأوامر والاجتناب عن النواهي. اللغة العربية تحصل على الضمان في الطقوس الثقافية بجزاء الأجر من استخدامها لقراءة القرآن الكريم. في كثير من الأحوال، كانت المراسيم الثقافية تستخدم اللغة العربية كثيرا بفضلها كما قام بها الأولياء في عملية الدعوة لدى المجتمع. يطور الأولياء التسعة الدعوة على حسب أحوال المجتمع في تحقيق المراسيم الدينية واستخدامهم اللغة العربية فيها. هوية المسلم متصفة بالأنشطة الدينية واللباس الظاهرة المنظورة بأحساسهم. استخدام لسان صدق سيكون متطلبا في الشخصية وتعميق مضمون القرآن الكريم والأحاديث النبوية. دور الأولياء التسعة في توسيع الدين الإسلامي بإندونيسيا لا ينطلق من تبسيط الطقوس المبنية على حفظ الجودة العبودية التي كانت المضامين الإسلامية وتياراتها تتبلغ كاملا. طقوس التهليل هي إحدى المراسيم الدينية التي تفيد دعاء الميت المصمم المناسبة بالثقافة المحلية مثل أربعين يوما، 100 يوم إلخ حيث كان المسلمون الإندونيسيون يعملون بها. التأثير في عملها مؤسس برسالة موصلة بالأدلة المستخدمة نظريا وتطبيقيا. Arabic language is a language that reflects the culture of Islam embodied in cultural rituals by servicing Allah in obedience to his orders and away from his prohibitions. Arabic language gets assurances in cultural rituals with rewards on its use for reciting the Qur’an. In many ways, religious ceremonies also often use arabic language with their virtues as well as the guardians in carrying out their dakwah to the people. Wali Songo develops dakwah based on the state of society in realizing the cultural ceremony and the using of Arabic language in it. The identity of a Muslim can be seen in religious activities and his clothes may appear visible to their senses. The use of good expressions to be guided in behaving and deepening the content of the Qur’an and al-Hadith. The role of Wali Songo in the Islamic religion in Indonesia can not be separated from the simplification of rituals built in maintaining the quality of worship which of course the nuances of Islam and its teachings must be delivered perfectly. The ritual of tahlil is one of the religious ceremonies that serves the praying of the dead who are packaged to adapt local culture such as 40 days, 100 days and so on which at present some Indonesian Muslim community do. The impetus to carry it out is based on a message conveyed by theoretical and applicable theorems.